A experiência da democracia participativa em Ribeirão Preto : estudo de caso no Conselho Municipal da Saúde - Rodrigues, Renato Cesar Assef (2017)
Encouraged by the Federal Constitution and the federal legislation that followed its promulgation, the experience of participatory democracy involved the creation of municipal councils, the holding of conferences, public consultations and hearings aimed at discussing public policies, the use of resources, and focuses of its and legitimacy of acts of the Public Power that require popular approval. Popular participation appears as a way to bring the citizen closer to the government and the opportunity of the real defense of collective interests, but whose realization is not without problems. The popular participation must overcome several obstacles in the search of its effectiveness not to become mere instrument of manipulation of the governments of turn in the sense of only legitimizing administrative practices and laws. Based on this scenario, the objectives of this work are: 1) to analyze from the theoretical point of view and the political discussion the advantages and limits of the concrete experience of implementing mechanisms and spaces of participatory democracy; 2) to analyze the experience of a particular context - Ribeirão Preto - by examining the institution, operation and performance of the City Health Council, especially in assessing the degree of popular intervention in the administrative actions discussed within this participatory institution. The expectation of this dissertation is to understand the effectiveness of the broad proposal of participatory democracy based on the analysis of a specific case that combines the area of Health, the scope of a council (deliberative) in a medium-sized municipality (Ribeirão Preto).